Techniki inkorporacji literatury oralnej w literaturze popularnej - Trocha, Bogdan (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The author in this article presents and discusses the techniques of introducing elements of oral literature by authors of popular literature. The starting point of this article is a discussion of the technique of using a magic fairy in fantasy. Starting from a very wide range of treatments, various motifs are in operation which are derived from magic fairies, before we move on to the analysis of the mechanisms used in stylistic re-narrations of content. We then discuss the techniques used in introducing archaic myths to fantasy literature . Here we present simple re-narration, ornamental operations, and interesting proposals related to mythopoeic literary speculation. Another type of reference to oral literature is the archaic epic, largely used in the context of aesthetic appeal, but there are also re-narrative and speculative novels in which the amount of information needed to understand the story forces the recipient of popular literature to return to the sources. The final mechanism discussed shows the functions of oral literature in science fiction.
Keywords: literatura popularna; fantasy; oralność; bajka magiczna